Four-level screening method for multi-variable truncation design of deepwater mooring system. (January 2017) - Wei, Handi; Xiao, Longfei; Tian, Xinliang; Kou, Yufeng
Abstract: The truncation design of a mooring system is the foundation of hybrid model testing techniques used in experimental research on deepwater floating platforms owing to the limited size of wave basin. Screening multi-variables for multi-objectives leads to difficulties in truncation design aimed at achieving acceptable equivalence, especially for an asymmetric mooring system. This paper proposes an efficient four-level screening method for the truncation design. The selected multi-variables of each mooring line are screened individually to generate feasible regions according to pretensions and initial hang-off angles. Subsequently, the feasible regions are concentrated by the second- and third-level screening: design truncated mooring lines and truncated mooring systems according to static equivalence. Finally, numerical forced oscillation is employed as the fourth-level screening to fulfil dynamic equivalence. Case studies of the truncation design of symmetric and asymmetric mooring systems have verified the proposed method. Highlights: An efficient four-level screening method is proposed for multi-variable truncation design of mooring systems. Feasible regions of selected multi-variables are screened and concentrated based on static equivalence. Numerical forced oscillations are employed to fulfill dynamic equivalence. The truncated models satisfactorily represent static and dynamic characteristics of full-depth mooring system.